Innovators in battery technology : profiles of 93 influential electrochemists - Desmond, Kevin, 1950- (McFarland & Company, Inc., 2016)
"This biographical dictionary profiles 85 electrochemists from 19 nations who during the past 270 years have researched and developed efficient batteries and energy cells. Each entry traces the subject's origin, education, discoveries and patents, hobbies and family life. The breakthroughs of early innovators are cataloged and the work of living scientists and technicians is brought up to date"--